Intracorneal Amphotericin B Injection in a Case of Indolent Candidal Keratitis - Deswal, Jyoti (J Clin Diagn Res, 2017)
Ocular candidiasis is one of the opportunistic infection occurring in human body. Pathogenesis wise, Candida is very virulent and slow growing organism. We report a case of 76-year-old female with left eye candidal stromal abscess, not responding to topical and oral antifungal drugs. Patient was administered intrastromal amphotericin B injection in the affected eye. Four midstromal injections were given in the areas surrounding the corneal abscess. A total of approximately 0.05 mL of amphotericin B, 5 μg per 0.1 mL, was administered. Within next four weeks, the eye became completely quiet with healed epithelial defect and corneal scarring. Intracorneal injection of amphotericin B is a safe and effective treatment option for recurrent and recalcitrant fungal infections.